2018
DOI: 10.3390/ma11040495
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Chemical Bonding of the Li-Doped Polar Intermetallic RE2In1−xLixGe2 (RE = La, Nd, Sm, Gd; x = 0.13, 0.28, 0.43, 0.53) System

Abstract: Four polar intermetallic compounds belonging to the RE2In1−xLixGe2 (RE = La, Nd, Sm, Gd; x = 0.13(1), 0.28(1), 0.43(1), 0.53(1)) system have been synthesized by the traditional solid-state reaction method, and their crystal structures have been characterized by single-crystal X-ray diffraction (SXRD) analyses. The isotypic crystal structures of four title compounds adopt the Mo2FeB2-type structure having the tetragonal space group P4/mbm (Z = 2, Pearson code tP40) with three crystallographically independent at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This type of site-preference is not as largely noticeable as that between Ca 2+ and Eu 2+ in our Ca 2– x Eu x CdSb 2 system due to the relatively smaller size difference between Ca 2+ ( r = 1.00 Å) and Yb 2+ ( r = 1.02 Å, both for the 6-coordinates). The atomic site-preference is normally understood either by the electronic-factor or by the size-factor criteria as previously reported in various Zintl phases including the Ca 11– x Yb x Sb 10– y Ge z (0 ≤ x ≤ 9; 0 ≤ y ≤ 3; 0 ≤ z ≤ 3), RE 11 Ge 4 In 6– x M x (RE = La, Ce; M = Li, Ge; x = 1, 1.96), Ca 5– x Yb x Al 2 Sb 6– y Ge y ( x = 0.2, 0.5, 0.7), and RE 2 In 1– x Li x Ge 2 (RE = La, Nd, Sm, Gd; x = 0.13, 0.28, 0.43, 0.53) . For the title Ca 2– x Eu x CdSb 2 system, we believe that the site-preference should be strongly affected by the size-factor criterion given the large size difference between Ca 2+ and Eu 2+ ( r (Eu 2+ ) = 1.17 Å for the 6-coordinates) resulting in the predominant Eu 2+ occupation at the M1-site.…”
Section: Resultsmentioning
confidence: 99%
“…This type of site-preference is not as largely noticeable as that between Ca 2+ and Eu 2+ in our Ca 2– x Eu x CdSb 2 system due to the relatively smaller size difference between Ca 2+ ( r = 1.00 Å) and Yb 2+ ( r = 1.02 Å, both for the 6-coordinates). The atomic site-preference is normally understood either by the electronic-factor or by the size-factor criteria as previously reported in various Zintl phases including the Ca 11– x Yb x Sb 10– y Ge z (0 ≤ x ≤ 9; 0 ≤ y ≤ 3; 0 ≤ z ≤ 3), RE 11 Ge 4 In 6– x M x (RE = La, Ce; M = Li, Ge; x = 1, 1.96), Ca 5– x Yb x Al 2 Sb 6– y Ge y ( x = 0.2, 0.5, 0.7), and RE 2 In 1– x Li x Ge 2 (RE = La, Nd, Sm, Gd; x = 0.13, 0.28, 0.43, 0.53) . For the title Ca 2– x Eu x CdSb 2 system, we believe that the site-preference should be strongly affected by the size-factor criterion given the large size difference between Ca 2+ and Eu 2+ ( r (Eu 2+ ) = 1.17 Å for the 6-coordinates) resulting in the predominant Eu 2+ occupation at the M1-site.…”
Section: Resultsmentioning
confidence: 99%
“…Finding a sustainable clean energy source is an enduring issue for humankind in modern society. Despite our continuous efforts to discover and develop various energy sources, we easily overlook the fact that about 67% of the energy we use is wasted in the form of heat. , Since thermoelectric (TE) materials can directly convert wasted heat sources into electricity, these materials and devices adapting TE materials have been considered as one of the smartest solutions for energy-recycling purposes. Among the numerous candidates for this TE application, the Zintl phase is considered an excellent candidate with respect to its intrinsically semiconducting property and complex crystal structure, both of which are required for good TE candidates. In particular, the Zintl-phase A 5 M 2 Pn 6 (A = Ca, Sr, Eu, and Yb; M = Al, Ga, and In; Pn = As, Sb, and Bi) series has been extensively investigated by worldwide researchers for TE applications. Our recent studies for the Zintl-phase Ca 5– x Yb x Al 2 Sb 6 (1.0 ≤ x ≤ 5.0) system revealed that some Yb-rich compounds having a particular range of composition initially adopted the Ca 5 Al 2 Bi 6 -type phase, but they underwent a phase transition to the Ca 5 Ga 2 As 6 -type phase through the annealing process . Moreover, their electrical transport properties were also shifted from metallic to semiconducting during this phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…New compounds and new synthetic approaches are the topic of four of the papers. Lithium-containing solid solutions of the polar intermetallic of RE 2 InGe 2 (RE = La, Nd, Sm, Gd) were investigated by You et al [3]. These new intermetallics crystallize in the Mo 2 FeB 2 structure type with Li substituting for In.…”
mentioning
confidence: 99%